Економічні засади формування маркетингової політики продовольчих компаній - Чеботарев, В.А. (Економіка промисловості, 2015)
Запропоновано матрицю маркетингового забезпечення виробничо-комерційної діяльності продовольчих компаній відповідно моделі споживчого маркетингу та прогнозованих економічних чинників маркетингового середовища. Це надало можливість обгрунтувати заходи стосовно формування і вдосконалення маркетингової політики продовольчих компаній загальнодержавного і регіонального рівнів. Предложена матрица маркетингового обеспечения производственно-коммерческой деятельности продовольственных компаний в соответствии с моделью потребительского маркетинга и прогнозируемыми экономическими факторами маркетинговой среды таких предпринимательских формирований. Это дало возможность обосновать меры по формированию и совершенствованию маркетинговой политики продовольственных компаний общегосударственного и регионального уровней. Analysis of general economic peculiarities of management in food sphere, as well as the issues, trends and prospects of the development of food complex of Ukraine give grounds to assert that food companies have become its determinative business institutions. The experience of developed countries shows that with the increasing of maturity of market economy the business results of such institutions increasingly depend on its marketing collateral. This objectively necessitates the need of analysis of the companies‟ marketing environment and, above all, the necessity to forecast its economic factors. As such, the following was predicted for Ukraine: slowdown of increase temps of overall volume of demand for food products with a tendency to stabilize them; increase of consumers‟ demand for quality, safety and ecological performance of food products; beginning of open competition between companies of national level, as well as between companies of regional levels. On the basis of development of a principle model of marketing provision of business of these institutions a matrix of marketing provision of industrial and commercial activity of food companies was built in accordance with the model of consumer marketing (business-consumer) that is generally accepted in the world marketing science and with prognosticated economic factors of marketing environment. It‟s essential component are the proposals for companies to manage organizational and economic measures for realization their industrial and commercial activity in line with the projected economic factors of marketing environment.This has made possible to ground the system of measures of forming and enhancing the marketing policy of food companies of Ukraine at national and regional levels (marketing commodity policy, marketing assortment policy, marketing pricing policy, quality policy, distribution policy) in the short, medium and long-term perspective.